Investigating usability guidelines in developing mobile application - Mohammed Siti Asma, Abd Aziz Noor Azah, Ariffin Asma Hanee (Universiti Pendidikan Sultan Idris, 2016)
Investigating usability guidelines in developing mobile application by Mohammed Siti Asma, Abd Aziz Noor Azah, Ariffin Asma Hanee,